Procrastination, self-efficacy and time management in an academic environment - Koncevičienė, Jolanta (Psichologija, 2017)
Studies researching the relationship between procrastination and self-efficacy produce ambiguous results. According to some researchers, the relationship is positive, according to others – negative, and still others claim that there is no relationship between the two. This suggests that the actual relationship between procrastination and self-efficacy might be moderated by a third variable. In this paper, time management was chosen as a potential candidate for such moderation. Thus the aim of this study is to asses the relationship between self-efficacy, procrastination and time management in an academic environment. The Procrastination Assessment Scale for Students (PASS) was used for measuring the academic procrastination, while the Motivated Strategies for Learning Questionnaire (MSLQ) was utilised to measure the academic self-efficacy and academic time management. Survey participants consisted of individuals studying at the following universities: Vilnius University, Vilniaus Gedimino Technikos University, Mykolas Romeris University and Lietuvos Edukologijos University. In total, 153 students (88 women, 63 men and 2 unspecified) were surveyed using the paper and pencil method. Participants were selected using the convenience sampling strategy. The average age of participants was 20.2 years (SD = 1.21). The methodology of this study consists of a correlation analysis and a moderation analysis. The results suggest that the relationship between academic procrastination and academic self-efficacy is moderated by the skills of academic time management. Among the students with high time management, the score of increasing self-efficacy corresponded with decreasing procrastination. On the opposite, students with low self-efficacy showed a different trend: with an increase in time management, procrastination was decreasing at first; yet later it began increasing. In general, the level of procrastination is lower when both self-efficacy and time management are high. The sample used in this study was quite homogeneous; therefore, the obtained results should be interpreted with some caution. Future work could be focused on repeating the same study using a more representative sample.